2015
DOI: 10.2152/jmi.62.56
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences of the influential factors on the mental health condition of teachers in the A university

Abstract: : The purpose of this research was to investigate the gender differences of the influential factors on the mental health condition among university teachers in the A university in Japan. A questionnaire survey was mailed to 924 university teachers in Japan, with a survey return rate of 43.8% % (N=405). The General Health Questionnaire 28 (GHQ-28), Multidimensional Scale of Perceived Social Support (MSPSS), the Japanese version of the Brief Coping Orientation to Problems Experienced (COPE) and the Work Situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
7
1
2
Order By: Relevance
“…Another study found out that 1/3 of female university graduates were overworked and showed resignation tendencies [25]. Additionally, the GHQ total score of female Japanese lecturers was found to be significantly higher than that of males [26]. Often-neglected relations between lecturers and students play an important role in university teachers' perceptions of exhaustion and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found out that 1/3 of female university graduates were overworked and showed resignation tendencies [25]. Additionally, the GHQ total score of female Japanese lecturers was found to be significantly higher than that of males [26]. Often-neglected relations between lecturers and students play an important role in university teachers' perceptions of exhaustion and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of the results for the BRUMS application, it is evident that there is a difference in the moods of men and women, already presented in other studies, as well as for the different age groups [7] [12] [14] [27]. Moreover, in the latter, there is a significant difference in all mood factors.…”
Section: Discussionmentioning
confidence: 59%
“…The Brief-COPE, developed by Carver et al , can measure a wide range of stress-coping mechanisms 18 , 19 ) . Although the Japanese version of the Brief-COPE developed by Otsuka et al has some limitations 20 ) , it is one of the most commonly used coping scales and is also used when surveying workers 21 , 22 ) . Coping is defined as the process of cognitive and behavioral efforts to deal with a request that is rated as beyond an individual’s resources 23 ) .…”
Section: Methodsmentioning
confidence: 99%